Luther on Jews and Judaism. A review of his "Judenschriften" - Wessels, Francois (Stellenbosch Theological Journal, 2018)
Luther on Jews and Judaism. A review of his "Judenschriften" by Paas, Steven. 2017, LIT VERLAG GmbH & Co. KG Wien. CH-8032 Zurich. ISBN 9783643909473